The relations “Italian State-Catholic Church” in the Lateran Pacts of 1929: historical and juridical considerations - NACCI, MATTEO (Prawo Kanoniczne, 2017)
This work is a conference in the Faculty of Canon Law of the Toulouse Catholic University that want to consider the relations between Italian go- vernment and Catholic Church in the Lateran Pacts of 1929, in an historical and juridical perspective, through the examination of the “preconciliazione” phase and the dierent political trends around to Lateran Pacts. e purpose of the study, in fact, is to underline the important “juridical culture” of this agreement in the European overview.